E-commerce from the customer panel: the phenomenon of the pandemic increase and future challenge - Jasińska-Biliczak, Anna (Business, Management and Economics Engineering, 2022)
Purpose – the purpose of the article is to present the customers (the auction site’s users) perception of the opportunities provided by e-commerce, especially increasing its meaning during the pandemic conditions and to conclude the ways of e-commerce development in the future.Research methodology – the methodology was based at desk research and the survey conducted in April 2021 among online users of Allegro on-line platform by the one of the basic quantity methods, the CAWI method (by the questionnaire survey) supported by statistic method. Findings – the increasing role of e-commerce in people’s lives as well as the pandemic increasing e-commerce growth effect, it can therefore be crucial for the country’s market position and its developmental perspectives. Some customers habits, especially greater savings regimes, more careful approach to spending, but also on-line shopping, will stay with them even after the pandemic.Research limitations – the research is limited to the leading, but one, on-line platform one of the TOP-10 on-line platforms however, because of the market coverage, it is representative for the examined branch. Other limitation is the pandemic period which may present the data characteristic only for this time.Practical implications – nowadays, especially developed by the pandemic and lockdown all over the world, the e-trade has spread its development. The practical implication may be using the results of the research in practice by the on-line shops owners/managers.Originality/Value – the value of the study is the realistic approach while attempting to provide a clear view of the overarching picture of the e-trade and directions of its development, especially after pandemic experience. The originality also is that the research conducted not only It has also shown that online commerce transactions are conducted not only at young people probe, but at the probe representative for whole society, including elderly people. The study fulfils the gap at e-commerce research due to the often proclaimed lack of attitude of older people towards e-commerce or pointing them as the age group’s digital exclusion.